Role of halal certification in business performance: A study of the kopitiams industry - Yusuf, Asnidar Hanim; Oyelakin, Oyewale Idris; Abdul Shukor, Syadiyah; Ahmad Bustamam, Ummi Salwa (2017)
Purpose - Halal certification has many benefits in terms of higher market segment (Liow, 2012; Husain et al., 2012; Said & Elangkovan, 2013), hygiene and safety (Syed Marzuki et al., 2012; Ahmad et al., 2013) and potential to gain interest from Muslim tourist all over the world to come to Malaysia (Ab Rahman Ilyia et al., 2011; Syed Marzuki et al., 2012).There is limited study that discuss on what benefit Halal certificate can do to business performance. Business owners are usually interested to invest in activities that bring direct benefit to their profitability and development of their business (Yusuf et al., 2016).To find the relationship between business performance and Halal certification or Halal implementation in food outlet, this research took the approach of qualitative study to gain more insight and gain information on experiences of the business owners of kopitiams in Selangor.The method chosen to get the information needed is case study for four selected kopitiams. The objective of this study is to explore why is Halal certificate important and how does it impact the business performance of the case studies in terms of Islamic value, social contribution, financial capital and human capital. The main result of the study concluded that Halal certificate does bring benefit in their business performance in terms of Islamic view, social contribution, financial capital and human capital. Halal certificate contributes as motivation for Muslim companies to gain religious benefit, provide customer satisfaction, opening up more job opportunities and avoid social problems. In financial capital, Halal certificate is seen as internal resource to boost sales and influence customers’ purchase decision.As for human capital, Halal certificate can help increase skill and development of the companies’ human resources. Methodology - Data collection in this study used two types of techniques; 1) Data collection with kopitiam business owners, managerial staff and operational staff 2) Focus group interview with consumers of the kopitiams to get insights on consumers’ perspectives of the issue being studied.The instruments that are used are semi structured open ended questions so that the respondents (kopitiam business owners, managerial staff, operational staff and consumers of the kopitiam) can focus on issues that should be raised by them instead of being restricted to researcher’s questions (Barbour, 2013).